Impact of Energy Drink Consumption on Sleep Quality of Medical Students - Zulfiqar, Fariha; Riaz, Saba; Arooj, Ayesha; Mazhar, Tooba; Gill, Muhammad Ahad (International Health Review, 2025)
The study aims to evaluate the impact of energy drink consumption on the sleep quality of the medical students of Lahore, Pakistan. A cross-sectional study design was employed and data were collected through convenience sampling. After taking informed consent, 236 MBBS students of both gender within the age range of 18-25 years filled the questionnaire. Quality of sleep was by assessed by using the Pittsburgh Sleep Quality Index. The mean age of students was 22.33 ± 1.47 years, with 94 (39.8%) male and 142 (60.2%) female students. Among these 236 participants, 110 (46.6%) were regular consumers of energy drinks, while 126 (53.4%) had not consumed any energy drink during the last 1 year. Out of 110 students who consumed energy drinks during the last 1 year, 21 (38.16%) reported good quality sleep. Among the 106 students who consumed energy drinks in the last 1 month, only 19 (17.92%) reported good quality sleep. These findings indicate that students who consumed energy drinks continuously in the last month had a higher percentage of poor sleep quality. The study concluded that the majority of students consuming energy drinks had poor sleep quality. This shows an association between energy drink consumption and poor sleep quality among students. The findings suggest that the students who consumed energy drinks in the past month were more likely to have difficulty in their sleep as compared to those who did not.